Cellular uptake and nuclear binding of insulin in human cultured lymphocytes: evidence for potential intracellular sites of insulin action. - Goldfine, I D (1977)
Human cultured lymphocytes (IM-9) were used to demonstrate that insulin can enter the intact cell and bind to the nucleus. When these lymphocytes were incubated with 125I-labeled insulin, specific cellular uptake reached a maximum within 2 min and remained at a plateau for 90 min or longer. Partially purified nuclei from such cells contained approximately 15-20% of the total cellular radioactivity. Nuclei freed of all other cellular fractions (by washing the partially purified nucleic with Triton X-100) bound approximately 7% of the total cellular radioactivity. In contrast to the rapid uptake of labeled insulin into the intact cell, specific binding to the nucleus was half-maximal after 5 min of incubation and maximal after 90 min. Both the cellular uptake and subsequent nuclear binding of labeled insulin were progressively inhibited by increasing concentrations of unlabeled hormone. Independent evidence for the nuclear binding of insulin was obtained by preparing autoradiographs of lymphocytes incubated for various times with labeled insulin. Such preparations strongly suggest that insulin binds to the plasma membrane, enters the cytosol, and then binds to the nucleus.